Development of a method for quantitative determination of γ-oryzanol using near infrared spectroscopy - Pungseeklao, Thitiwat; Opanasopit, Praneet; Khuwijitjaru, Pramote (Food and Applied Bioscience Journal, 2017)
γ-Oryzanol is a natural bioactive component found in rice bran oil. Quantitative analysis of the compound is usually done by UV-spectrophotometric or chromatographic methods. This study evaluated the potential of near infrared spectroscopy (NIRS) transmission analysis for determining γ-oryzanol in commercial rice bran oil using standard γ-oryzanol in 3 different solvent systems, i.e. in hexane, in purified medium chain fatty acids (MCF), and in hexane containing 10% MCF. The results showed that NIRS analysis using standard γ-oryzanol in hexane allowed estimation of γ-oryzanol content in commercial rice bran oil with higher accuracy than the others. The predicted performance of the developed model measured by the ratio of performance to deviation (RPD) was 5.93, which indicated that the method effectively provided an alternative for determination of γ-oryzanol in rice bran oil.